2005
DOI: 10.1242/jcs.01607
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic glycosaminoglycan mimetic (RGTA) modifies natural glycosaminoglycan species during myogenesis

Abstract: Crucial events in myogenesis rely on the highly regulated spatiotemporal distribution of cell surface heparan sulfate proteoglycans to which are associated growth factors, thus creating a specific microenvironment around muscle cells. Most growth factors involved in control of myoblast growth and differentiation are stored in the extracellular matrix through interaction with specific sequences of glycosaminoglycan oligosaccharides, mainly heparan sulfate (HS). Different HS subspecies revealed by specific antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
0
21
0
1
Order By: Relevance
“…One of the molecular mechanisms of such an effect probably relies on a direct binding of glycosaminoglycan mimetics to RANTES/CCL5, which could result in an inhibition of the chemokine binding to glycosaminoglycans carried by proteoglycans expressed at the cell surface. However, it has been shown that the glycosaminoglycan mimetic cell treatment induced the changes in glycosaminoglycan amount, composition, and localization in C2.7 myoblast cultures undergoing differentiation (19). Therefore, it cannot be excluded that, in the present study, OTR4120 or OTR4131 could also interfere by this way with RANTES binding to the cells, resulting in the decreased chemotactic effects.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…One of the molecular mechanisms of such an effect probably relies on a direct binding of glycosaminoglycan mimetics to RANTES/CCL5, which could result in an inhibition of the chemokine binding to glycosaminoglycans carried by proteoglycans expressed at the cell surface. However, it has been shown that the glycosaminoglycan mimetic cell treatment induced the changes in glycosaminoglycan amount, composition, and localization in C2.7 myoblast cultures undergoing differentiation (19). Therefore, it cannot be excluded that, in the present study, OTR4120 or OTR4131 could also interfere by this way with RANTES binding to the cells, resulting in the decreased chemotactic effects.…”
Section: Discussionmentioning
confidence: 64%
“…Synthetic polymers, called RGTA (for regenerating agent; refs. 19,20,30), have been engineered to mimic the stabilizing properties of glycosaminoglycans toward heparin-binding growth factors. OTR4120 and OTR4131 were tested in our assays.…”
Section: Effect Of Synthetic Glycosaminoglycan Mimetics On Rantes Binmentioning
confidence: 99%
“…Synthesis of OTR4120-OTR4120 is a carboxymethyl-dextran sulfate with a degree of substitution of 1.13 for sulfate residues and 0.46 for carboxymethyl residues, for a maximal degree of substitution of 3.0 (29,30). These substitution degrees are similar to those assayed in heparin used as a control.…”
Section: Methodsmentioning
confidence: 88%
“…OTR4120 was covalently bound to BSA in a potassium phosphate buffer (0.2 M, pH 8) medium as previously described. 40 The protein concentration was determined by the kit BCA protein assay (Pierce). The surface of 96 flat-well were coated overnight at 41C with 100 ml of OTR4120-BSA (20 mg/ml of equivalent BSA), prepared complexes in 50 mM TrisHCl, pH 7.4, supplemented with 12.5 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%